Pengaruh Himbauan Pajak, Pemeriksaan Pajak dan Penagihan Pajak Terhadap Tingkat Kepatuhan Wajib Pajak dalam Pelunasan Pajak Penghasilan Badan - Abdul rauf; Amir Mahmud; Yuliana Yuliana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
That the government's policy in increasing domestic revenue for financing development and public services from the tax sector, among others, is through changing the official assessment levy system to a self-assessment, namely by giving trust to taxpayers to calculate, deposit and self-report taxes owed in accordance with tax regulations. through the submission of an annual notification letter. Annual notification letter is a means for taxpayers to report all business activities of taxpayers during a certain period. As a consequence, the Directorate General of Taxes is obliged to provide services, supervision, guidance and law enforcement, among others through the issuance of tax appeals, tax audit processes and tax collection actions. This study uses quantitative research through a survey method based on a Likert scale by distributing questionnaires to respondents as many as 28 statements. The population used is corporate taxpayers who pay corporate income tax at the office, totaling 104 taxpayers as a sample of all registered taxpayers. Because this research method is parametric statistics, while the research questionnaire made using a Likert scale which is an ordinal scale and is usually used in non-parametric statistical methods, before processing the data obtained is first converted from ordinal data to interval data using the Method of Succesive Interval ( MSI). Data processing was carried out using the IBM SPSS version 26 application. The results showed that partial tax appeals have a positive effect on taxpayer compliance, partial tax audits have a positive effect on taxpayer compliance, partial tax collections have a positive effect on taxpayer compliance and tax appeals, joint tax audits and tax collections, they have a positive influence on taxpayer compliance in the payment of Corporate Income Tax at the Palembang Intermediate Tax Service Office.